Infant Social Avoidance Predicts Autism but Not Anxiety in Fragile X Syndrome - Roberts, Jane E.; Crawford, Hayley; Will, Elizabeth A.; Hogan, Abigail L.; McQuillin, Samuel; Tonnsen, Bridgette L.; O'Connor, Shannon; Roberts, Douglas A.; Brewe, Alexis M. (Frontiers in Psychiatry, 2019)
Objective: Autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD) and anxiety are three of the most common childhood psychiatric disorders. Early trajectories of social avoidance have been linked with these psychiatric disorders in previous studies, but it remains unclear how social avoidance differentially predicts comorbid disorders in a high-risk genetic subgroup. Here, we delineate the association between trajectories of social avoidance from infancy and subsequent ASD, ADHD, and anxiety outcomes at preschool in children with fragile X syndrome (FXS), a well-characterized single-gene disorder highly associated with social avoidance as well as elevated rates of ASD, ADHD, and anxiety. Method: Males with FXS (n = 78) ages 4-62 months participated in a longitudinal study resulting in 201 assessments. The Social Avoidance Scale (SAS) documented socially avoidant behaviors from infancy in three domains – physical movement, facial expression, and eye contact during both the first minute and the last hour of an interaction. ASD, ADHD, and anxiety symptom outcomes at preschool were measured via parent-report questionnaires. Results: Increased social avoidance across infancy and preschool predicted elevated ASD symptom severity but reduced ADHD and anxiety symptom severity in males with FXS. Conclusion: ASD, ADHD and anxiety symptoms relate inconsistently to social avoidance behaviors, providing new insight toward the debate of independence or overlap among these disorders in FXS and other disorders (i.e., ASD). The results suggest that the nuanced profile of the developmental and temporal aspects of social avoidance may inform more the accuracy of differential diagnoses of comorbid psychiatric disorders in FXS.